1996
DOI: 10.1111/j.1532-5415.1996.tb04068.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Importance of Strength and Balance in Chair Rise by Functionally Impaired Older Individuals

Abstract: Lower extremity strength and balance control both play a role in performance of chair rise; lower extremity strength is the stronger predictor of success for functionally impaired older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
124
3
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(133 citation statements)
references
References 9 publications
2
124
3
4
Order By: Relevance
“…Lower-extremity strength of the hip and knee is a significant predictor of the ability to perform these activities [1,[12][13]. In a study examining the influence of hip and knee strength and hip power, Bean et al found that isometric hip extensor strength was the strongest predictor of the amount of time that functionally impaired adults would require to complete five chair rises [12].…”
Section: Introductionmentioning
confidence: 99%
“…Lower-extremity strength of the hip and knee is a significant predictor of the ability to perform these activities [1,[12][13]. In a study examining the influence of hip and knee strength and hip power, Bean et al found that isometric hip extensor strength was the strongest predictor of the amount of time that functionally impaired adults would require to complete five chair rises [12].…”
Section: Introductionmentioning
confidence: 99%
“…TUG tasks demands one to interact with the surrounding environment, as well as have integrative upper/lower-limb movement with a coordinated cognitive process. In general, when patients perform the TUG test, they need to have the neuromuscular-skeletal components of agility, flexibility, balance, and strength [12,18,19]. This present study sought to investigate any relationship between the TUG performance time and CAL in chronic stroke survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects are concentrating on consecutive tasks in order to balance while performing sit-to stand, turning around and returning to the starting point [18]. To do this, they need to have the neural muscular skeletal components of strength, agility, flexibility, and balance [12,18,19]. There is complex relationship between the attentional demands to control motor performance and the performance in daily living.…”
Section: Introductionmentioning
confidence: 99%
“…The activities proposed by the TUG need strength, agility, and balance 23,24 . Thus, smaller values indicate better functional mobility, better balance, increased gait speed and, therefore, a minor risk of falling, as well as a possible greater independence in daily life activities.…”
Section: Discussionmentioning
confidence: 99%